Experimental and theoretical investigations on the phase stability and mechanical properties of Cr7Mn25Co9Ni23Cu36 high-entropy alloy. (15th April 2021) - Qin, Gang; Chen, Ruirun; Mao, Huahai; Yan, Yan; Li, Xiaojie; Schönecker, Stephan; Vitos, Levente; Li, Xiaoqing
Abstract: Understanding the mechanisms of phase formation and their influence on the mechanical behavior is crucial for materials used in structural applications. Here, the phase decomposition under heat treatment in the Cr7 Mn25 Co9 Ni23 Cu36 (atomic percentage) high-entropy alloy and how secondary phases formed affect its tensile mechanical response are reported. The microstructural analysis shows that heat treatment at 800 °C /2 h and 600 °C /8 h led to the formation of sigma phase, but the sigma phase was not observed for 2 h heat treatment at 600 °C and below. The experimentally observed thermal stability and phases are compared to the calculated phase diagram and rationalized by recourse to thermodynamics and kinetics. The mechanism of phase decomposition is discussed based on ab initio calculations, indicating that decomposition into two solid solution phases is energetically preferred over a single solid solution phase with nominal composition. Graphical abstract: Image, graphical abstract